A gangue-based permeable filling material and mine water purification method thereof

By using coal gangue-based permeable filling materials in the goaf, the permeable filling filter layer is constructed, and the mine water pollution problem caused by coal mining is solved, and the mine water self-purification and efficient utilization of gangue solid waste are achieved.

CN118754480BActive Publication Date: 2025-04-01CHINA UNIV OF MINING & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410788825.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-04-01
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

The mine influx caused by coal mining contains a large amount of organic matter and heavy metals, causing water pollution, affecting ecological security and wasting mine water resources.

Method used

The coal gangue-based permeable filling material is used. The material consists of 65-80% coal gangue aggregate, 15-30% activated coal gangue powder, 2-4% alkali trigger, 0.5-1% molecular additive and 4-6% water. By building a permeable filling filter layer in the goaf, it can efficiently absorb heavy metals in the mine water and reduce the mineralization degree of the mine water.

Benefits of technology

It has achieved self-purification of mine water in the goaf, improved the utilization rate of gangue solid waste, reduced the mineralization degree of mine water, and has good promotion prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754480B_ABST
    Figure CN118754480B_ABST
Patent Text Reader

Abstract

The present invention discloses a gangue-based permeable filling material and a mine water purification method thereof, and belongs to the field of green mining and environmentally friendly materials. The preparation method of the gangue-based permeable filling material is as follows: firstly, the gangue is crushed, ground, calcined, and mechanochemically modified to obtain activated gangue powder; then, the gangue aggregate, activated gangue powder, alkali activator, molecular additive, and water are mixed and stirred to obtain the gangue-based permeable filling material. The mine water purification method thereof is as follows: the permeable filling material is filled into the goaf by using a filling coal mining hydraulic support to form a permeable filling filter layer with a thickness of 5-50 meters, and the mine water is purified after being filtered through the permeable filling layer. The permeable filling material of the present invention has good permeability, excellent mechanical properties, strong adsorption performance for heavy metals such as Cu, Pb, Cr in mine water, and reduces the mineralization of mine water. The present invention can solve the problem of mine water disposal while realizing the utilization of gangue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of green mining and environmentally friendly materials, and specifically relates to a gangue-based water-permeable filling material and a mine water purification method thereof. Background Art

[0002] A large amount of coal gangue will be produced in the process of coal resource development and utilization. The disposal of coal gangue in mining areas has become an important issue restricting the coordinated development of coal resources and the environment.

[0003] Coal mining causes the overlying rock strata to move and deform, resulting in a large number of cracks. The water resources in the aquifer penetrate into the goaf through the cracks, forming mine water. Since the goaf contains a large amount of organic matter and heavy metals such as Cu, Pb, and Cr, the mine water quality is seriously polluted. Long-term discharge will cause groundwater, river channels and soil pollution around the mining area, seriously affecting ecological safety and causing a large amount of mine water resources. Therefore, how to purify mine water and improve its comprehensive utilization rate is a key issue that needs to be solved urgently.

[0004] Based on this, the present invention proposes a gangue-based permeable filling material and a mine water purification method thereof, which has multiple functions of gangue solid waste disposal and mine water self-purification in the goaf. By constructing a gangue-based permeable filling filter layer in the goaf, heavy metals such as Cu, Pb, and Cr in the mine water can be efficiently absorbed, the mineralization of the mine water can be reduced, and the self-purification of the mine water in the goaf can be achieved, in order to provide a new material and purification method for the large-scale utilization of gangue solid waste and mine water disposal. Summary of the invention

[0005] Purpose of the invention: In view of the deficiencies in the prior art, the present invention provides a gangue-based permeable filling material and a mine water purification method thereof, which improves the utilization of gangue solid waste, efficiently adsorbs heavy metal pollutants such as Cu, Pb, Cr in mine water, and achieves the dual purpose of solid waste disposal and coordinated mine water self-purification in goafs.

[0006] Technical solution: To achieve the above purpose, the technical solution adopted by the present invention is:

[0007] The first object of the present invention is to provide a gangue-based permeable filling material, the components of which include, by weight percentage: 65-80 parts of gangue aggregate, 15-30 parts of activated gangue powder, 2-4 parts of alkali activator, 0.5-1 parts of molecular additives and 4-6 parts of water, wherein:

[0008] The activated coal gangue powder is obtained by crushing, grinding and calcining coal gangue, and then subjected to mechanochemical modification. The mechanochemical modification is to mix a chemical modifier with the coal gangue powder, stir and ball mill. The chemical modifier includes at least one of acetic acid, citric acid, formic acid and tartaric acid.

[0009] In the present invention, activated gangue powder, alkali activator and molecular additives are added to gangue aggregate, and the prepared gangue-based permeable filling material has the characteristics of high porosity, good adsorption performance and excellent mechanical properties. On the one hand, the present invention uses activated gangue powder to cooperate with alkali excitation to improve the activity of gangue, and the gel formed by alkali-activated gangue powder has a high specific surface area and interlayer spacing; on the other hand, by adding polydimethyldiallylammonium chloride and polyacrylamide molecular additives, adsorption functional groups can be formed on the surface of the pores inside the permeable porous filling material, thereby increasing the adsorption performance of the gangue-based permeable filling material.

[0010] Optionally, in one embodiment of the present invention, the coal gangue aggregate has a particle size of 5-40 mm, which is convenient for filling pipeline pumping.

[0011] Optionally, in one embodiment of the present invention, the coal gangue is crushed and ground to a particle size of less than 200 meshes to obtain coal gangue powder. The coal gangue powder at this time has a larger specific surface area, which improves its hydration reaction activity.

[0012] Optionally, in one embodiment of the present invention, the calcination temperature is 600-800° C. This calcination temperature can effectively remove organic components and volatile substances in the coal gangue and improve the volcanic ash activity of the coal gangue.

[0013] Optionally, in one embodiment of the present invention, the chemical modifier includes at least one of acetic acid, citric acid, formic acid, and tartaric acid. Acidification modification can increase the specific surface area of ​​the powder material and increase its hydration activity. At the same time, the acid used is safe, easy to obtain, and relatively cheap. In other examples, other types of acids can also be used for modification, all of which belong to the protection scope of the present invention.

[0014] Further optionally, the chemical modifier is a mixture of acetic acid, citric acid, formic acid and tartaric acid.

[0015] Further optionally, in one embodiment of the present invention, the components of the chemical modifier include, by weight percentage: 30-60 parts of acetic acid, 20-50 parts of citric acid, 10-30 parts of formic acid, and 15-25 parts of tartaric acid.

[0016] Optionally, in one embodiment of the present invention, the weight ratio of the chemical modifier to the coal gangue powder is 1:10 to 1:5. This ratio is relatively moderate, and too high or too low will have a negative impact on the performance of the filling material.

[0017] Further optionally, in one embodiment of the present invention, the weight ratio of the chemical modifier to the coal gangue powder is 1:10.

[0018] Optionally, in one embodiment of the present invention, the chemical modifier and the coal gangue powder are mixed and stirred for 3-5 minutes.

[0019] Optionally, in one embodiment of the present invention, the rotation speed of the ball mill is 400-520 r / min, and the ball milling time is 20-30 min.

[0020] Further optionally, in one embodiment of the present invention, the rotation speed of the ball mill is 520 r / min, and the ball milling time is 30 min.

[0021] Optionally, in one embodiment of the present invention, the mechanochemical modification process is to mix 10 parts by weight of a chemical modifier with 100 parts of coal gangue powder and stir for 3-5 minutes; pour into a ball mill, set the speed to 520r / min, and obtain activated coal gangue powder after 30 minutes of ball milling.

[0022] Optionally, in one embodiment of the present invention, the alkaline activator includes at least one of sodium hydroxide and sodium silicate. Sodium hydroxide and sodium silicate as alkaline activators have the advantages of being environmentally friendly, safe, and inexpensive, and can effectively promote the hydration reaction.

[0023] Further optionally, in one embodiment of the present invention, the components of the alkaline activator include 10-15 parts of sodium hydroxide and 2-20 parts of sodium silicate by weight.

[0024] Optionally, in one embodiment of the present invention, the molecular additive includes at least one of a silane coupling agent, polydimethyldiallyl ammonium chloride, and polyacrylamide. The silane coupling agent can react the groups of inorganic and organic substances to enhance the adhesion between the two; polydimethyldiallyl ammonium chloride and polyacrylamide can form adsorption functional groups on the internal surface of the material to enhance the adsorption performance.

[0025] Further optionally, in one embodiment of the present invention, the molecular additive includes a silane coupling agent and further includes polydimethyldiallylammonium chloride and / or polyacrylamide.

[0026] Further optionally, in one embodiment of the present invention, the components of the molecular additive include, by weight, 0.02-0.08 parts of a silane coupling agent, 0.1-0.4 parts of polydimethyldiallylammonium chloride, and 0.2-0.5 parts of polyacrylamide.

[0027] Optionally, in one embodiment of the present invention, the molecular weight of the polydimethyldiallylammonium chloride is 400,000-500,000, and the molecular weight of the polyacrylamide is 12 million-15 million.

[0028] The second object of the present invention is to provide a method for preparing a gangue-based water-permeable filling material as described above, comprising the following steps:

[0029] a. Mixing and stirring the activated gangue powder and the gangue aggregate to obtain a mixed dry material;

[0030] b. mixing the molecular additive, the base activator and water to obtain a mixed solution;

[0031] c. Pour the mixed solution into the mixed dry materials and stir to obtain the gangue-based water-permeable material.

[0032] Optionally, in one embodiment of the present invention, in step a, the components include 65-80 parts by weight of coal gangue aggregate and 15-30 parts by weight of activated coal gangue powder.

[0033] Optionally, in one embodiment of the present invention, in step b, the components include 0.5-1 parts of molecular additives, 2-4 parts of base activators and 4-6 parts of water by weight.

[0034] Optionally, in one embodiment of the present invention, the particle size of the coal gangue aggregate is 5-40 mm.

[0035] Optionally, in one embodiment of the present invention, in step a, the activated coal gangue powder is obtained by crushing, grinding and calcining coal gangue, and then subjected to mechanochemical modification. The mechanochemical modification is to mix a chemical modifier with the coal gangue powder, stir and ball mill, and the chemical modifier includes at least one of acetic acid, citric acid, formic acid and tartaric acid.

[0036] Optionally, in one embodiment of the present invention, the coal gangue has a particle size of less than 200 mesh after crushing and grinding.

[0037] Optionally, in one embodiment of the present invention, the calcination temperature is 600-800°C.

[0038] Optionally, in one embodiment of the present invention, the chemical modifier is a mixture of acetic acid, citric acid, formic acid and tartaric acid, and the composition ratio by weight is: (30-60): (20-50): (10-30): (15-25).

[0039] Optionally, in one embodiment of the present invention, the mechanochemical modification process is to mix 10 parts by weight of a chemical modifier with 100 parts of coal gangue powder and stir for 3-5 minutes; pour into a ball mill, set the speed to 520r / min, and obtain activated coal gangue powder after 30 minutes of ball milling.

[0040] Optionally, in one embodiment of the present invention, the molecular additive is silane coupling agent, polydimethyldiallylammonium chloride, and polyacrylamide, and the composition ratio thereof is (0.02-0.08) in parts by weight: (0.1-0.4) in parts by weight: (0.2-0.5).

[0041] Optionally, in one embodiment of the present invention, the molecular weight of the polydimethyldiallylammonium chloride is 400,000-500,000, and the molecular weight of the polyacrylamide is 12 million-15 million.

[0042] Optionally, in one embodiment of the present invention, the alkaline activator is sodium hydroxide and sodium silicate, and the composition ratio thereof is (10-15): (2-20) by weight.

[0043] Optionally, in one embodiment of the present invention, in step a, the activated coal gangue powder and coal gangue aggregate are mixed and stirred for 3-5 minutes.

[0044] Optionally, in one embodiment of the present invention, in step b, the molecular additive, alkaline activator and water are mixed and stirred for 2-3 minutes.

[0045] Optionally, in one embodiment of the present invention, in step c, the mixed solution is poured into the mixed dry materials and stirred for 5-10 minutes.

[0046] The third object of the present invention is to provide an application of the gangue-based permeable filling material as described in any one of the above or the gangue-based permeable filling material prepared by the method described in any one of the above in the field of green mining or environmental protection materials.

[0047] Optionally, in one embodiment of the present invention, the compressive strength of the gangue-based permeable filling material is not less than 1.4 MPa.

[0048] Further optionally, in one embodiment of the present invention, the compressive strength of the gangue-based permeable filling material is 1.4-1.8 MPa.

[0049] Optionally, in one embodiment of the present invention, the water seepage height of the gangue-based permeable filling material is not less than 37 mm.

[0050] Further optionally, in one embodiment of the present invention, the water seepage height of the gangue-based permeable filling material is 37-42 mm.

[0051] Optionally, in one embodiment of the present invention, the gangue-based permeable filling material has an adsorption capacity of 0.003%-0.004% for the heavy metal element Cu in mine water, and / or

[0052] The adsorption capacity of heavy metal element Pb in mine water reaches 0.002%-0.003%, and / or

[0053] The adsorption capacity of heavy metal element Cr in mine water reaches 0.003%-0.004%, wherein the adsorption capacity refers to the percentage of heavy metal element content in the elements contained in the filling paste.

[0054] Optionally, in one embodiment of the present invention, the reduction rate of the coal gangue-based permeable filling material on the mineralization of mine water is not less than 20%.

[0055] Further optionally, in one embodiment of the present invention, the reduction rate of the coal gangue-based permeable filling material on the mineralization of mine water is 20% to 40%.

[0056] The fourth object of the present invention is to provide a method for purifying mine water by using gangue-based permeable filling materials. The operation method is: using a filling mining hydraulic support to fill the gangue-based permeable filling material into the goaf to form a permeable filling filter layer, and the mine water is purified after passing through the permeable filling filter layer. The gangue-based permeable filling material is a gangue-based permeable filling material as described in any one of the above items, or a gangue-based permeable filling material prepared by the method described in any one of the above items.

[0057] In the present invention, by constructing a gangue-based permeable filling and filtration layer in the goaf, organic impurities and heavy metals such as Cu, Pb, Cr in mine water can be efficiently absorbed, the mineralization of mine water can be reduced, and self-purification of mine water in the goaf can be achieved, which has a good promotion prospect.

[0058] Optionally, in one embodiment of the present invention, the water permeable filling and filtration layer has a thickness of 5-50 m.

[0059] Beneficial effects: Compared with the prior art, the gangue-based permeable filling material and mine water purification method provided by the present invention have the following advantages:

[0060] 1. Using coal gangue as raw material realizes the large-scale disposal and utilization of gangue solid waste, which is green, economical and environmentally friendly;

[0061] 2. By adding alkali activators and molecular additives, the porosity of the filling material is increased, and it has better adsorption and mechanical properties;

[0062] 3. The permeable filling and filtration layer constructed in the goaf area using coal gangue-based filling materials can efficiently absorb heavy metals such as Cu, Pb, Cr in the mine water, reduce the mineralization of the mine water, and achieve self-purification of the mine water in the goaf area, which has a good promotion prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1It is a schematic diagram of the gangue-based filling material and the mine water purification method thereof of the present invention;

[0064] In the figure: 1—aquifer; 2—fracture zone; 3—goaf; 4—mine water; 5—purified mine water; 6—gangue-based permeable filling material. DETAILED DESCRIPTION

[0065] The purpose of the present invention is to provide a method for purifying mine water using gangue-based permeable filling materials, which aims to improve the utilization of gangue solid waste, increase the permeability and adsorption performance of filling materials, reduce the content of organic impurities and heavy metals such as Cu, Pb, Cr in mine water, and achieve the dual purposes of large-scale utilization of gangue solid waste and mine water purification.

[0066] The embodiment of the present invention is a gangue-based water-permeable filling material and a mine water purification method thereof, which belongs to the field of green mining and environmentally friendly materials. In the embodiment of the present invention, the gangue-based water-permeable filling material comprises: 65-80 parts of gangue aggregate, 15-30 parts of activated gangue powder, 2-4 parts of alkali activator, 0.5-1 parts of molecular additives and 4-6 parts of water, wherein:

[0067] The activated coal gangue powder is obtained by crushing, grinding, calcining and mechanochemical modification of coal gangue, wherein the mechanochemical modification is to mix and stir a chemical modifier with the coal gangue powder and then ball mill the chemical modifier, wherein the chemical modifier comprises at least one of acetic acid, citric acid, formic acid and tartaric acid;

[0068] The components of the chemical modifier include, by weight percentage: 30-60 parts of acetic acid, 20-50 parts of citric acid, 10-30 parts of formic acid, and 15-25 parts of tartaric acid;

[0069] The components of the alkaline activator include, by weight: 10-15 parts of sodium hydroxide, 2-20 parts of sodium silicate;

[0070] The components of the molecular additive include, by weight: 0.02-0.08 parts of silane coupling agent, 0.1-0.4 parts of polydimethyldiallyl ammonium chloride (PDADMAC), and 0.2-0.5 parts of polyacrylamide (PAM).

[0071] In an embodiment of the present invention, a method for preparing a gangue-based water-permeable filling material is as follows:

[0072] a. Mix the activated gangue powder and gangue aggregate and stir for 3-5 minutes to obtain a mixed dry material;

[0073] b. Mix the molecular additive, base activator and water and stir for 2-3 minutes to obtain a mixed solution;

[0074] c. Pour the mixed solution into the mixed dry materials and stir for 5-10 minutes to obtain the gangue-based permeable material.

[0075] In an embodiment of the present invention, a method for purifying mine water by using gangue-based permeable filling materials is as follows: permeable filling materials are filled into the goaf using a filling mining hydraulic support to form a 5-50m permeable filling filter layer, and the mine water is purified after passing through the permeable filling filter layer.

[0076] The present invention is further described below in conjunction with the embodiments and patent drawings:

[0077] Comparative Example 1

[0078] In this comparative example, no alkali activator was added, and the purpose was to study the effect of the alkali activator on the gangue-based permeable filling material.

[0079] a. Weigh 10 parts of chemical modifier and 100 parts of coal gangue powder, mix and stir for 5min, pour into a ball mill, set the speed to 520r / min, and mill for 30min to obtain activated coal gangue powder;

[0080] b. Mix 65 parts of gangue aggregate with 15 parts of activated gangue powder and stir for 3 min to obtain a mixed dry material;

[0081] c. Mix 0.5 parts of the molecular additive with 4 parts of water and stir for 2 minutes to obtain a mixed solution;

[0082] d. Pour the mixed solution into the mixed dry material and stir for 5 minutes to obtain the gangue-based permeable filling material.

[0083] Then, in order to detect the mechanical characteristics, permeability and heavy metal adsorption capacity of the filling materials, the filling materials were subjected to simulated curing and corresponding tests, as follows:

[0084] Pour the filling slurry into a triple mold with a size of 70.7*70.7*70.7mm, put it on a vibrator and oscillate for 30 seconds. Demould it after 24 hours, put it in a curing box with a temperature of 20°C and a humidity of 95%, and cure it for 28 days to obtain test specimens, and take a part of the test specimens for uniaxial compressive strength test.

[0085] A layer of melted paraffin with a small amount of rosin is coated on the side of a portion of the test pieces, and then the test pieces are pressed into the test mold with a pressurizer. The water seepage height of the test pieces is tested using a fully automatic water penetration tester with a set water pressure of 1.2 MPa and a pressurization time of 24 hours.

[0086] The remaining specimens were sprayed with mine water at a flow rate of 0.2 L / min and a spray time of 10 days. Some specimens before and after spraying were placed in a drying oven at 60°C for 48 hours and ground to less than 200 mesh. Inductively coupled plasma mass spectrometry (ICP-MS) was used to test the contents of Cu, Pb, and Cr elements in the samples before and after spraying.

[0087] Take 100 mL of mine water before and after spraying, place it in a weighed evaporating dish, evaporate it to dryness on a water bath, then put it in an oven and dry it at 105°C for 2 hours, place it in a desiccator to cool to room temperature, weigh it, and repeat the drying and weighing until constant weight is achieved (the difference between two weighings should not exceed 0.0002 g).

[0088] Comparative Example 2

[0089] This comparative example does not add molecular additives, and is intended to study the effects of molecular additives on coal gangue-based permeable filling materials.

[0090] a. Weigh 10 parts of chemical modifier and 100 parts of coal gangue powder, mix and stir for 5min, pour into a ball mill, set the speed to 520r / min, and mill for 30min to obtain activated coal gangue powder;

[0091] b. Mix 65 parts of gangue aggregate with 15 parts of activated gangue powder and stir for 3 min to obtain a mixed dry material;

[0092] c. Mix 2 parts of the base activator with 4 parts of water and stir for 2 minutes to obtain a mixed solution;

[0093] d. Pour the mixed solution into the mixed dry material and stir for 5 minutes to obtain the gangue-based permeable filling material.

[0094] Then, in order to detect the mechanical characteristics, permeability and heavy metal adsorption capacity of the filling materials, the filling materials were subjected to simulated curing and corresponding tests, as follows:

[0095] Pour the filling slurry into a triple mold with a size of 70.7*70.7*70.7mm, put it on a vibrator and oscillate for 30 seconds. Demould it after 24 hours, put it in a curing box with a temperature of 20°C and a humidity of 95%, and cure it for 28 days to obtain test specimens, and take a part of the test specimens for uniaxial compressive strength test.

[0096] A layer of melted paraffin with a small amount of rosin is coated on the side of a portion of the test pieces, and then the test pieces are pressed into the test mold with a pressurizer. The water seepage height of the test pieces is tested using a fully automatic water penetration tester with a set water pressure of 1.2 MPa and a pressurization time of 24 hours.

[0097] The remaining specimens were sprayed with mine water at a flow rate of 0.2 L / min and a spray time of 10 days. Some specimens before and after spraying were placed in a drying oven at 60°C for 48 hours and ground to less than 200 mesh. Inductively coupled plasma mass spectrometry (ICP-MS) was used to test the contents of Cu, Pb, and Cr elements in the samples before and after spraying.

[0098] Take 100 mL of mine water before and after spraying, place it in a weighed evaporating dish, evaporate it to dryness on a water bath, then put it in an oven and dry it at 105°C for 2 hours, place it in a desiccator to cool to room temperature, weigh it, and repeat the drying and weighing until constant weight is achieved (the difference between two weighings should not exceed 0.0002 g).

[0099] Comparative Example 3

[0100] In this comparative example, no alkali activator and molecular additive were added, and the purpose was to study the effects of the alkali activator and molecular additive on the gangue-based permeable filling material.

[0101] a. Weigh 10 parts of chemical modifier and 100 parts of coal gangue powder, mix and stir for 5min, pour into a ball mill, set the speed to 520r / min, and mill for 30min to obtain activated coal gangue powder;

[0102] b. Mix 65 parts of gangue aggregate with 15 parts of activated gangue powder and stir for 3 min to obtain a mixed dry material;

[0103] c. Pour 4 parts of water into the mixed dry materials and stir for 5 minutes to obtain the gangue-based permeable filling material.

[0104] Then, in order to detect the mechanical characteristics, permeability and heavy metal adsorption capacity of the filling materials, the filling materials were subjected to simulated curing and corresponding tests, as follows:

[0105] Pour the filling slurry into a triple mold with a size of 70.7*70.7*70.7mm, put it on a vibrator and oscillate for 30 seconds. Demould it after 24 hours, put it in a curing box with a temperature of 20°C and a humidity of 95%, and cure it for 28 days to obtain test specimens, and take a part of the test specimens for uniaxial compressive strength test.

[0106] A layer of melted paraffin with a small amount of rosin is coated on the side of a portion of the test pieces, and then the test pieces are pressed into the test mold with a pressurizer. The water seepage height of the test pieces is tested using a fully automatic water penetration tester with a set water pressure of 1.2 MPa and a pressurization time of 24 hours.

[0107] The remaining specimens were sprayed with mine water at a flow rate of 0.2 L / min and a spray time of 10 days. Some specimens before and after spraying were placed in a drying oven at 60°C for 48 hours and ground to less than 200 mesh. Inductively coupled plasma mass spectrometry (ICP-MS) was used to test the contents of Cu, Pb, and Cr elements in the samples before and after spraying.

[0108] Take 100 mL of mine water before and after spraying, place it in a weighed evaporating dish, evaporate it to dryness on a water bath, then put it in an oven and dry it at 105°C for 2 hours, place it in a desiccator to cool to room temperature, weigh it, and repeat the drying and weighing until constant weight is achieved (the difference between two weighings should not exceed 0.0002 g).

[0109] Comparative Example 4

[0110] This comparative example does not add chemical modifiers, and is intended to study the effects of chemical modifiers on coal gangue-based permeable filling materials.

[0111] a. Pour 100 parts of coal gangue powder into a ball mill, set the speed to 520r / min, and obtain coal gangue powder after 30min of ball milling;

[0112] b. Mix 65 parts of gangue aggregate with 15 parts of gangue powder and stir for 3 minutes to obtain a mixed dry material;

[0113] c. Mix 0.5 parts of the molecular additive with 4 parts of water and stir for 2 minutes to obtain a mixed solution;

[0114] d. Pour the mixed solution into the mixed dry material and stir for 5 minutes to obtain the gangue-based permeable filling material.

[0115] Then, in order to detect the mechanical characteristics, permeability and heavy metal adsorption capacity of the filling materials, the filling materials were subjected to simulated curing and corresponding tests, as follows:

[0116] Pour the filling slurry into a triple mold with a size of 70.7*70.7*70.7mm, put it on a vibrator and oscillate for 30 seconds. Demould it after 24 hours, put it in a curing box with a temperature of 20°C and a humidity of 95%, and cure it for 28 days to obtain test specimens, and take a part of the test specimens for uniaxial compressive strength test.

[0117] A layer of melted paraffin with a small amount of rosin is coated on the side of a portion of the test pieces, and then the test pieces are pressed into the test mold with a pressurizer. The water seepage height of the test pieces is tested using a fully automatic water penetration tester with a set water pressure of 1.2 MPa and a pressurization time of 24 hours.

[0118] The remaining specimens were sprayed with mine water at a flow rate of 0.2 L / min and a spray time of 10 days. Some specimens before and after spraying were placed in a drying oven at 60°C for 48 hours and ground to less than 200 mesh. Inductively coupled plasma mass spectrometry (ICP-MS) was used to test the contents of Cu, Pb, and Cr elements in the samples before and after spraying.

[0119] Take 100 mL of mine water before and after spraying, place it in a weighed evaporating dish, evaporate it to dryness on a water bath, then put it in an oven and dry it at 105°C for 2 hours, place it in a desiccator to cool to room temperature, weigh it, and repeat the drying and weighing until constant weight is achieved (the difference between two weighings should not exceed 0.0002 g).

[0120] Example 1

[0121] a. Weigh 10 parts of chemical modifier and 100 parts of coal gangue powder, mix and stir for 5min, pour into a ball mill, set the speed to 520r / min, and mill for 30min to obtain activated coal gangue powder;

[0122] b. Mix 65 parts of gangue aggregate with 15 parts of activated gangue powder and stir for 3 min to obtain a mixed dry material;

[0123] c. Mix 2 parts of base activator, 0.5 parts of molecular additive and 4 parts of water and stir for 2 minutes to obtain a mixed solution;

[0124] d. Pour the mixed solution into the mixed dry material and stir for 5 minutes to obtain the gangue-based permeable filling material.

[0125] Then, in order to detect the mechanical characteristics, permeability and heavy metal adsorption capacity of the filling materials, the filling materials were subjected to simulated curing and corresponding tests, as follows:

[0126] Pour the filling slurry into a triple mold with a size of 70.7*70.7*70.7mm, put it on a vibrator and oscillate for 30 seconds. Demould it after 24 hours, put it in a curing box with a temperature of 20°C and a humidity of 95%, and cure it for 28 days to obtain test specimens, and take a part of the test specimens for uniaxial compressive strength test.

[0127] A layer of melted paraffin with a small amount of rosin is coated on the side of a portion of the test pieces, and then the test pieces are pressed into the test mold with a pressurizer. The water seepage height of the test pieces is tested using a fully automatic water penetration tester with a set water pressure of 1.2 MPa and a pressurization time of 24 hours.

[0128] The remaining specimens were sprayed with mine water at a flow rate of 0.2 L / min and a spray time of 10 days. Some specimens before and after spraying were placed in a drying oven at 60°C for 48 hours and ground to less than 200 mesh. Inductively coupled plasma mass spectrometry (ICP-MS) was used to test the contents of Cu, Pb, and Cr elements in the samples before and after spraying.

[0129] Take 100 mL of mine water before and after spraying, place it in a weighed evaporating dish, evaporate it to dryness on a water bath, then put it in an oven and dry it at 105°C for 2 hours, place it in a desiccator to cool to room temperature, weigh it, and repeat the drying and weighing until constant weight is achieved (the difference between two weighings should not exceed 0.0002 g).

[0130] Example 2

[0131] a. Weigh 10 parts of chemical modifier and 100 parts of coal gangue powder, mix and stir for 5min, pour into a ball mill, set the speed to 520r / min, and mill for 30min to obtain activated coal gangue powder;

[0132] b. Mix 72 parts of gangue aggregate with 20 parts of activated gangue powder and stir for 4 minutes to obtain a mixed dry material;

[0133] c. Mix 3 parts of base activator, 0.7 parts of molecular additive and 5 parts of water and stir for 3 minutes to obtain a mixed solution;

[0134] d. Pour the mixed solution into the mixed dry material and stir for 7 minutes to obtain the gangue-based permeable filling material.

[0135] Then, in order to detect the mechanical characteristics, permeability and heavy metal adsorption capacity of the filling materials, the filling materials were subjected to simulated curing and corresponding tests, as follows:

[0136] Pour the filling slurry into a triple mold with a size of 70.7*70.7*70.7mm, put it on a vibrator and oscillate for 30 seconds. Demould it after 24 hours, put it in a curing box with a temperature of 20°C and a humidity of 95%, and cure it for 28 days to obtain test specimens, and take a part of the test specimens for uniaxial compressive strength test.

[0137] A layer of melted paraffin with a small amount of rosin is coated on the side of a portion of the test pieces, and then the test pieces are pressed into the test mold with a pressurizer. The water seepage height of the test pieces is tested using a fully automatic water penetration tester with a set water pressure of 1.2 MPa and a pressurization time of 24 hours.

[0138] The remaining specimens were sprayed with mine water at a flow rate of 0.2 L / min and a spray time of 10 days. Some specimens before and after spraying were placed in a drying oven at 60°C for 48 hours and ground to less than 200 mesh. Inductively coupled plasma mass spectrometry (ICP-MS) was used to test the contents of Cu, Pb, and Cr elements in the samples before and after spraying.

[0139] Take 100 mL of mine water before and after spraying, place it in a weighed evaporating dish, evaporate it to dryness on a water bath, then put it in an oven and dry it at 105°C for 2 hours, place it in a desiccator to cool to room temperature, weigh it, and repeat the drying and weighing until constant weight is achieved (the difference between two weighings should not exceed 0.0002 g).

[0140] Example 3

[0141] a. Weigh 10 parts of chemical modifier and 100 parts of coal gangue powder, mix and stir for 5min, pour into a ball mill, set the speed to 520r / min, and mill for 30min to obtain activated coal gangue powder;

[0142] b. Mix 80 parts of gangue aggregate with 30 parts of activated gangue powder and stir for 5 minutes to obtain a mixed dry material;

[0143] c. Mix 4 parts of base activator, 1 part of molecular additive and 6 parts of water and stir for 3 minutes to obtain a mixed solution;

[0144] d. Pour the mixed solution into the mixed dry material and stir for 10 minutes to obtain the gangue-based permeable filling material.

[0145] Then, in order to detect the mechanical characteristics, permeability and heavy metal adsorption capacity of the filling materials, the filling materials were subjected to simulated curing and corresponding tests, as follows:

[0146] Pour the filling slurry into a triple mold with a size of 70.7*70.7*70.7mm, put it on a vibrator and oscillate for 30 seconds. Demould it after 24 hours, put it in a curing box with a temperature of 20°C and a humidity of 95%, and cure it for 28 days to obtain test specimens, and take a part of the test specimens for uniaxial compressive strength test.

[0147] A layer of melted paraffin with a small amount of rosin is coated on the side of a portion of the test pieces, and then the test pieces are pressed into the test mold with a pressurizer. The water seepage height of the test pieces is tested using a fully automatic water penetration tester with a set water pressure of 1.2 MPa and a pressurization time of 24 hours.

[0148] The remaining specimens were sprayed with mine water at a flow rate of 0.2 L / min and a spray time of 10 days. Some specimens before and after spraying were placed in a drying oven at 60°C for 48 hours and ground to less than 200 mesh. Inductively coupled plasma mass spectrometry (ICP-MS) was used to test the contents of Cu, Pb, and Cr elements in the samples before and after spraying.

[0149] Take 100 mL of mine water before and after spraying, place it in a weighed evaporating dish, evaporate it to dryness on a water bath, then put it in an oven and dry it at 105°C for 2 hours, place it in a desiccator to cool to room temperature, weigh it, and repeat the drying and weighing until constant weight is achieved (the difference between two weighings should not exceed 0.0002 g).

[0150] Test Case

[0151] The test blocks obtained from each comparative example and embodiment were tested for uniaxial compressive strength, water seepage height, heavy metal content and mineralization content. The results are shown in Table 1.

[0152] Table 1 Experimental results

[0153]

[0154] From the above results, it can be found that compared with Comparative Example 1 and Comparative Example 3 which do not use alkali activator, the strength of the filling paste in Examples 1-3 after being treated with alkali activator is significantly higher than that in Comparative Example 1 and Comparative Example 3, and the penetration height is also significantly higher than that in Comparative Example 1 and Comparative Example 3, indicating that the alkali activator can increase the reaction activity of coal gangue, stimulate the activated coal gangue powder to form a gel with a higher interlayer spacing, thereby improving the mechanical properties and permeability properties of the filling material.

[0155] Compared with Comparative Example 4 in which no chemical modifier was used, the strength of the filling paste in Examples 1-3 after using chemical modifiers to activate the coal gangue powder was significantly higher than that in Comparative Example 4, indicating that the chemical modifier can stimulate the hydration activity of the coal gangue powder, thereby improving the mechanical strength of the filling paste.

[0156] Compared with Comparative Example 2 and Comparative Example 3 in which no molecular additives were added, after adding molecular additives to Examples 1-3, the adsorption capacity of Cu, Pb, and Cr elements by the filling paste increased, and the mineralization of mine water decreased significantly (Examples 1-3 were 21.4%, 29.5%, and 36.5%, respectively), indicating that after adding molecular additives, the adsorption performance of the filling paste on heavy metal elements in mine water was improved, and the mineralization of mine water was reduced.

[0157] The above results indicate that the gangue-based permeable filling material of the present invention has excellent mechanical properties, good water permeability, strong adsorption capacity for heavy metals, and can effectively reduce the mineralization of mine water.

[0158] Application Example 1

[0159] A gangue-based permeable filling material and a method for purifying mine water thereof, such as Figure 1 As shown, the steps are as follows:

[0160] 1. Use the filling coal mining hydraulic support to fill the gangue-based permeable filling material 6 into the goaf 3 to construct a gangue-based permeable filling filter layer with a thickness of 25m;

[0161] 2. Water in the aquifer 1 penetrates into the goaf 3 through the through fractures in the fracture zone 2, forming mine water 4;

[0162] 3. When the organic impurities, heavy metals, etc. in the mine water 4 pass through the gangue-based permeable filling material, the organic impurities, heavy metals, etc. in the mine water 4 are filtered and adsorbed to obtain purified mine water 5.

[0163] In this embodiment, a permeable filling and filtration layer is constructed in the goaf using coal gangue-based filling materials, and the amounts of Cu, Pb, and Cr absorbed in the mine water are 0.002%, 0.003%, and 0.003%, respectively. The mineralization of the mine water is reduced by 3.28 g / L, and the self-purification of the mine water in the goaf is achieved, which has a good promotion prospect.

[0164] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above-mentioned implementation mode, but also include technical schemes composed of any combination of the above-mentioned technical features. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.

Claims

1. A gangue-based permeable filling material, characterized in that: The components thereof include, by weight: 65-80 parts of coal gangue aggregate, 15-30 parts of activated coal gangue powder, 2-4 parts of alkali activator, 0.5-1 parts of molecular additives and 4-6 parts of water, wherein: The components of the molecular additive include, by weight, 0.02-0.08 parts of silane coupling agent, 0.1-0.4 parts of polydimethyldiallylammonium chloride, and 0.2-0.5 parts of polyacrylamide; The activated coal gangue powder is obtained by crushing, grinding and calcining coal gangue to obtain coal gangue powder, and then subjected to mechanochemical modification, wherein the mechanochemical modification is to mix a chemical modifier with the coal gangue powder, stir and ball mill, and the chemical modifier includes at least one of acetic acid, citric acid, formic acid and tartaric acid; The particle size of the coal gangue aggregate is 5-40 mm; The gangue-based permeable filling material is used to purify mine water. The method for purifying mine water by the gangue-based permeable filling material comprises: using a filling mining hydraulic support to fill the gangue-based permeable filling material into the goaf to form a permeable filling filter layer, and the mine water is purified after passing through the permeable filling filter layer, and the thickness of the permeable filling filter layer is 5-50m; The compressive strength of the gangue-based permeable filling material is 1.4-1.8 MPa; The water seepage height of the gangue-based permeable filling material is 37-42 mm.

2. The gangue-based water-permeable filling material according to claim 1, characterized in that: The coal gangue is crushed and ground to a particle size of less than 200 mesh; and / or The calcination temperature is 600-800°C; and / or The components of the chemical modifier include, by weight: 30-60 parts of acetic acid, 20-50 parts of citric acid, 10-30 parts of formic acid, and 15-25 parts of tartaric acid; and / or The weight ratio of the chemical modifier to the coal gangue powder is 1:10 to 1:5; and / or The mixing time of the chemical modifier and the coal gangue powder is 3-5 minutes; and / or The ball mill has a rotation speed of 400-520 r / min and a ball milling time of 20-30 min.

3. The gangue-based water-permeable filling material according to claim 1, characterized in that: The alkaline activator includes at least one of sodium hydroxide and sodium silicate.

4. The gangue-based water-permeable filling material according to claim 3, characterized in that: The components of the alkaline activator include 10-15 parts of sodium hydroxide and 2-20 parts of sodium silicate by weight.

5. The gangue-based water-permeable filling material according to claim 1, characterized in that: The molecular weight of the polydimethyldiallylammonium chloride is 400,000-500,000, and the molecular weight of the polyacrylamide is 12 million-15 million.

6. The method for preparing a gangue-based water-permeable filling material according to any one of claims 1 to 5, characterized in that: The following steps are involved: a. Mixing activated gangue powder and gangue aggregate to obtain a mixed dry material, wherein the activated gangue powder is obtained by crushing, grinding and calcining the gangue, and then subjected to mechanochemical modification, wherein the mechanochemical modification is to mix and stir a chemical modifier with the gangue powder and ball mill, wherein the chemical modifier comprises at least one of acetic acid, citric acid, formic acid and tartaric acid; b. The molecular additive, the base activator and water are mixed and stirred to obtain a mixed solution; c. Pour the mixed solution into the mixed dry materials and stir to obtain the gangue-based permeable filling material.

7. The method according to claim 6, characterized in that In step a, the activated gangue powder and the gangue aggregate are mixed and stirred for 3-5 min; and / or In step b, the molecular additive, the base activator and water are mixed and stirred for 2-3 minutes; and / or In step c, the mixed solution is poured into the mixed dry materials and stirred for 5-10 min.

8. Application of gangue-based permeable filling materials in the field of green mining or environmental protection materials, wherein the gangue-based permeable filling materials are the gangue-based permeable filling materials as described in any one of claims 1 to 5, or the gangue-based permeable filling materials prepared by the method as described in any one of claims 6 to 7.

Citation Information

Patent Citations

  • Mine filling cementing material prepared by utilizing industrial by-product gypsum and preparation method for mine filling cementing material

    CN105753418A

  • Coal gangue-based C-A-S-H gel, preparation method and application

    CN115970636A

  • Mine water corrosion resistant coal-based solid waste filling paste and preparation method thereof

    CN117567091A

  • Coal gangue modified heavy metal adsorbent and preparation method thereof

    CN117696021A

  • Water purification method for coal mine worked-out section

    CN1482078A